A study of the spillover effects of digital financial agglomeration on economic resilience - Zhu, Zhiming; Yang, Yuanyuan; Li, Hongyan (Frontiers in Applied Mathematics and Statistics, 2023)
Digital finance is the combination of digital information technology and traditional finance. And digital financial agglomeration plays a pivotal role in the process of improving economic resilience in the new era. This paper introduces digital financial agglomeration, measures the economic resilience of each province and conducts spatial correlation tests by using 30 inter-provincial (except Hainan Province) panel data from 2011 to 2020, and constructs a Spatial Durbin Model to empirically analyze the relationship between digital financial agglomeration and economic resilience based on the theory of diffusion effect of digital financial agglomeration and research hypotheses. The results show that: (1) Digital financial agglomeration can have a positive effect on economic resilience by expanding the scale of consumption. (2) Digital financial agglomeration has a direct effect on the economic resilience of the region and an indirect spillover effect on the economic resilience of neighboring regions. (3) The effects of the main explanatory variables on economic resilience pass the robustness test: the positive effects of digital financial agglomeration, consumption scale and the interaction term of the two on economic resilience are significant. Finally, this paper proposes feasible practical suggestions for how to optimize the positive effect of digital financial agglomeration on economic resilience from the perspectives of increasing digital financial construction, popularizing digital financial knowledge and formulating differentiated strategies.